Pelatihan Pembuatan Produk Minyak Atsiri Berbahan Limbah Daun Cengkeh untuk Mengatasi Nyeri Gigi - Lameky, Vernando Yanry; Akollo, Isak Roberth; Djarami, Jayanti; Kolibonso, Billy Franscois; Pattinasarany, Devan Hendrik (Empowerment, 2024)
Teeth that are not well cared for can cause toothache. Tooth pain can interfere daily human activities. Tooth pain can be treated by traditional medicine. One plant that can be processed to treat toot pain is clove leaves. Clove leaves can be processed into essential oil which is useful in treating toothache. The results of discussions with the Mahia Hamlet community show that there are several problems that must be resolved in the Community Partnership Empowerment (CPE) program. These problems are 1) the lack of community skills to process traditional medicinal plants, clove leaf waste through the distillation process. 2) lack of knowledge and skills in using appropriate technology (TTG), especially kettles (distillation equipment) to produce essential oils. This CPE activity aims to increase knowledge and skills in using appropriate technology, especially kettles (distillation equipment) to produce essential oils. The CPE results show that the community has knowledge and skills about how to distill clove leaf essential oil which can be used in the treatment of toothache.